(untitled) (Economics and region, 2023)
The issue of ensuring social and economic security of the state was updated. It was substantiated the priority of applying a protective approach to ensuring the socio-economic security of the state under martial law conditions, the imperative concept of which is «threat». It was determined the essence of threats to the socio-economic security of the state as phenomena, trends and factors that prevent or make impossible the realization of the national economic interests and negatively affect the standard of living. The dialectic interrelationship of challenges, risks and threats as the main security factors was established. It was substantiated that socio-economic security ensuring under the protective approach consists in neutralizing risks and threats to the social component of Ukraine’s economic security. They are the forms of danger and reduce the level of security. It was proven the priority of monitoring threats in the war conditions and the global challenges growing influence. The indicator approach to threats identification was characterized. It consists in comparing the actual values of the socio-economic indicators with the characteristic (limit) values established by the official methodology. The actual values of the main Ukrainian socio-economic security indicators were calculated. Systemic threats in the social sphere were identified using the method of comparative and trend analysis. Challenges and threats to the socio-economic security of Ukraine under martial law conditions were identified. The threats with the maximum impact were analyzed. There is the drop in the living standard and the population impoverishment due to a rapid decline in the Ukrainians purchasing power; the unemployment growth due to the drop in business activity; the population displacement and the permanent employment loss due to the migration crisis. It was proved the necessity of forming an effective mechanism for ensuring the state socio-economic security based on the protective and sustainable approach and minimizing the threats negative impact.